Analisis Tata Niaga Rotan di Kelurahan Batu Kecamatan Pitu Riase Kabupaten Sidenreng Rappang - Erviyani Erviyani; Makkarennu Makkarennu; Muhammad Alif Kaimuddin Sahide; Asar Said Mahbub (Jurnal Hutan dan Masyarakat, 2017)
This study have purpose to determine the rattan trading channel and rattan trading functions, to know the interests of actors who play a role in every channel of rattan commerce and to know the power relations of each actor in the rattan trading channel. The research was conducted in February 2017 with the research location in Batu Village Pitu Riase Sub-District Sidenreng Rappang Regency. Sampling was done by purposive sampling with farmer sample as many as 5 samples. For the involved trading institutions are determined by a search method in which 3 collectors sample sample and 1 sample of wholesalers. The data used are primary data and secondary data. Method of data analysis used is descriptive analysis to analyze farmer selling price and buying price of intermediary trader and to know the interest and relation of actor who play role in rattan trading channel. The results conclude that there is one trade channel in the research area, namely: farmers - collectors traders - wholesalers. The results of operational efficiency analysis show that the trading system channel is not efficient yet. The reason is the farmers still play a role as the recipient of the price. The level of importance between the actors on the rattan trading channel in Batu Village is different. Of the three elements of power (trust, incentive and coercion) can be concluded that the actors are influential and have the highest power of traders (industry).